Popper’s fasificationism and his objections to marxism - Tovar Samanez, Carlos Miguel (2019)
Popper’s falsificationist method establishes criteria for demarcation between science and metaphysics, and proposes a procedure to test the validity of scientific theories. From his epistemological standpoint, Popper formulates critics to Marxism, and disapproves it with several arguments. This paper has the aim to analyze that argumentation and to determine if it is possible, using the same tools supplied by Popper, to validate the Marxist method, its capacity to formulate scientific rules, to make predictions founded in such rules and to resist the historical testing of those forecasts.